PERAN GURU UNTUK MENINGKATKAN KECERDASAN INTERPERSONAL ANAK USIA DINI PADA KEGIATAN OUTDOOR LEARNING - Erra Yuni Rindiani; Sumarno; Ida Dwijayanti (STKIP Subang, 2024)
This research aims to illustrate the role of teachers in enhancing the interpersonal intelligence of early childhood through outdoor learning activities, utilizing a qualitative descriptive research method. The research approach involves participatory observation, in-depth interviews with teachers, and the analysis of curriculum-related documents and outdoor learning activities. The findings indicate that the teacher's role in this context encompasses various aspects significantly contributing to the development of interpersonal intelligence in early childhood. As the primary facilitator, teachers guide children in outdoor activities, foster social interaction, and promote the development of interpersonal relationships. Teachers also play a crucial role in creating an environment supportive of collaborative learning, where children can learn together, share ideas, and overcome challenges collectively. This research highlights the importance of the teacher's role as a social model inspiring and guiding positive behavior in children. Moreover, the research findings can be implemented as a guide for curriculum development and the execution of outdoor learning activities to enhance the aspects of interpersonal intelligence in early childhood. The results of this study are expected to contribute to both practical and theoretical understanding of how this learning approach can be optimally integrated into the context of early childhood education.